The Bruyset´s bookshop at 1780 - Clemente San Román, Yolanda (Revista General de Información y Documentación, 2012)
This article presents a study of the European bookselling trade and the preferences of the readers through a detailed description of the catalogue of the books in Latin, English, Spanish and Italian that were on sale by the printers and booksellers Jean Marie I and Jean Marie II Bruyset. A language classification of the book stock is detailed, emphasasing both the period of publication and the subject of the reviewed prints. Furthermore, due to its singularity, the most significant editions and group of books in English are closely viewed as a sign of the interest these booksellers had in order to expand their business and develop trade relations with the Anglo-Saxon market.